PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH MOTIVASI INTRINSIK, KECERDASAN EMOSIONAL DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN TAMAN PEMALANG - Naniek Yulaizah, 12.5202.0170 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study examined the role of the Moderating Effect of Organizational Culture Intrinsic Motivation, Emotional Intelligence and competence professionel on Performance of State High School Teachers in District Taman. The specific objectives of the study is to examine how the Moderating Role of Organizational Culture Influence Intrinsic Motivation , Emotional Intelligence and competence professionel on Performance Teachers in District Taman. This study describes the usability and extend previous research on the Effect of Intrinsic Motivation Emotional Intelligence and competence professionel on Performance Master. The population in this study were high school teachers in the district TamanÂ  State totaling 156 people. In this study using primary data obtained by questionnaire. The research method using a computerized approach to the statistical program SPSS ( Statistical Package for Social Science ). The method of data analysis used linear regression to test the moderating effects. The results showed that intrinsic motivation has a positive and significant impact on performance. Emotional intelligence has is not positive and not significant impact on performance. Competence Professionel has a positive and significant impact on performance .. Organizational culture moderates the effect of intrinsic motivation has an effect on performance is not positive and not significant. While organizational culture moderates the influence of emotional intelligence is not significant to the performance of teachers. Organizational culture moderates the effec of competence professional is not significant to the performance of theachers..Keywords : organizational culture, intrinsic motivation, emotional intelligence, competence professional, performance and moderation.